Reimagining Islamic Education: Gus Dur’s Vision For Multiculturalism And Social Harmony In Indonesian Pesantren - Hifdil Islam, Muhammad; Aziz, Abd (LP3M UNZAH GENGGONG, 2025)
This article explores the multicultural educational philosophy of KH. Abdurrahman Wahid (Gus Dur), a prominent Muslim intellectual and former president of Indonesia, focusing on the strategic role of pesantren (Islamic boarding schools) in fostering inclusive, tolerant, and pluralistic values. Drawing from Gus Dur’s concept of pribumisasi Islam (indigenization of Islam), the study highlights how pesantren serve not only as religious institutions but also as cultural hubs for social transformation, interfaith dialogue, and democratic engagement. By introducing three core strategies—politico-cultural, socio-cultural, and pedagogical—the paper emphasizes the importance of integrating multiculturalism into Islamic education to counter rising religious intolerance and exclusivism. Gus Dur’s vision positions pesantren as pivotal agents of peacebuilding and civic education, where diversity is embraced as a divine gift. His ideas remain highly relevant in today’s context, offering a transformative model for Islamic education that aligns with Indonesia’s pluralistic identity and the universal values of justice, human dignity, and coexistence.